The Influence of Parental Involvement in Provision of Teaching –Learning Resources on Educational Outcomes: An Empirical Study of Teso North Sub County Primary Schools - Ndiku, Judah M (Advances in Social Sciences Research Journal, 2015)
The idea for parental involvement in education has come about as response to low students’ academic achievement amid claims that parents are not supportive. Parental involvement in provision of teaching and learning resources has been associated with positive achievements in educational outcomes. This study therefore examined the effect of parental involvement in provision of teaching and learning resources on academic performance in public primary schools in Teso North Sub County, Busia- Kenya. A descriptive survey research design was employed. Simple random sampling was used to select thirty schools. Proportionate random sampling was used to select one hundred and ninety two teachers and two hundred and eighty pupils while purposive sampling was used to select thirty head teachers and parents who served as respondents. Data was collected using questionnaires, semi- structured interviews schedules and document analysis. Data was analyzed using Microsoft excel and Stata. Quantitative data was analyzed using means, percentages and frequencies and qualitative data was reported directly. Pearson correlation coefficient and OLS regression coefficients were used to measure the degree of relationship. Statistical tests were done at α=0.05. The study revealed low parental involvement in provision of teaching and learning resources. There was a significant relationship between parental involvement in payment of access, PTA teachers and school academic performance. It was recommended that parents should be advised to support schools so as to realize improved educational outcomes.